2020
DOI: 10.1111/odi.13488
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and Zagreb earthquakes as stressors in patients with temporomandibular disorders

Abstract: Objective To evaluate stress effect of COVID‐19 pandemic and Zagreb earthquakes on symptoms of temporomandibular disorders (TMD). Materials and Methods One hundred and two previously diagnosed TMD patients were contacted by email to participate in an online survey about impact of those events on current and/or new symptoms, perceived stress, anxiety and symptom intensity in time‐points at the baseline, following pandemic and following earthquake. We compared data between earthquake‐affected and non‐affected re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
5
11
1
1
Order By: Relevance
“…As revealed in this study and earlier studies, a global stressor event (e.g. COVID-19 pandemic, war) can strongly affect the life of patients with TMDs [20][21][22][23][24]. Our results revealed that participants who presented with chronic TMD before the COVID-19 pandemic were more susceptible to COVID-related stress in comparison to those with acute/subacute TMD.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…As revealed in this study and earlier studies, a global stressor event (e.g. COVID-19 pandemic, war) can strongly affect the life of patients with TMDs [20][21][22][23][24]. Our results revealed that participants who presented with chronic TMD before the COVID-19 pandemic were more susceptible to COVID-related stress in comparison to those with acute/subacute TMD.…”
Section: Discussionsupporting
confidence: 78%
“…The prospective research methodology allowed us to examine the correlation between stress and the observed variables in addition to the correlation between stress and the variation of observed variables during the lockdown period. This methodological aspect is relevant as it allowed us to understand not only if people with TMD were affected by COVID-19 related stress (as previous studies have examined), but how they were affected [ 23 , 24 ]. Thus, our study is the first prospective study to report how a global stressor can influence people with TMD in relation to their general health, oral behaviours, psychosocial features, disability and pain intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant evaluation can identify the psychological information of patients. Such evaluation can help understand the pain and disability problems of patients who were affected by co-occurrence of COVID-19 and natural disasters (27). In addition, COVID-19 pandemic which is reinforced by disastrous events affected people's mental health remarkably.…”
Section: Earthquakes and Covid-19mentioning
confidence: 99%